2018
DOI: 10.4236/ce.2018.912131
|View full text |Cite
|
Sign up to set email alerts
|

The Pre and Final Year Dental Students’ Attitudes, Perception towards Postgraduate Specialization in Kinshasa University—Dental Medicine Department/DR. Congo

Abstract: The health professions are always affected by changes in the community, economics, religions, and politics. The aim of this study was to investigate the occurrence attitudes towards postgraduate specialization, and possible influencing factors for choosing specialties by the pre and final year students of Kinshasa University-Dental Medicine Department. A prospective survey of pre and final year dental students of Kinshasa University was carried out. Age, gender, nationality, and the occupation of parent's vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…According to Fidele et al 25 the motivation for pursuing specialization as career includes financial reasons followed by social status among public. Similarly study by Al-Bitar 26 showed that talent in a particular field is the main factor that can influence a student's decision for specialization.…”
Section: Discussionmentioning
confidence: 99%
“…According to Fidele et al 25 the motivation for pursuing specialization as career includes financial reasons followed by social status among public. Similarly study by Al-Bitar 26 showed that talent in a particular field is the main factor that can influence a student's decision for specialization.…”
Section: Discussionmentioning
confidence: 99%
“…(2018) hacen referencia al alto costo, el tiempo extenso del desarrollo y la interrupción del estilo de vida 27 , la ausencia de mentoría, falta de realismo en la expectativa y fricción personal con los docentes. 28 En el Perú se reportan algunos otros factores que complementan a los anteriores, como la oferta académica limitada de la universidades peruanas, por ejemplo las especialidades de Medicina y Patología Estomatológica, Auditoría Odontológica y Salud Pública Estomatológica, son solo ofertadas por la Universidad Peruana Cayetano Heredia 29 , no existiendo formación para Administración y Gestión en Estomatología, Implantología Oral Integral y Salud Familiar y Comunitaria en Odontología a pesar de su reconocimiento con el COP; la alternativa al elevado costo de los programas de posgrado en Segunda Especialidad es la modalidad de Residentado Odontológico (donde el Estado a través de una IPRESS financia la formación de profesionales a diferencia de la modalidad Ordinaria donde el estudiante corre con todo el financiamiento), pero este aún tiene una cantidad mínima de vacantes ofertadas, concentrada solo en tres sedes docentes (Universidad Peruana 51 Cayetano Heredia, Universidad Nacional Mayor de San Marcos y el Universidad Nacional Federico Villareal) y todos ubicados en la ciudad de Lima, que resulta en una limitante para los estudiantes.…”
Section: Discussionunclassified
“…Oral and maxillofacial surgery (OMFS) is considered a dental specialty in most African countries, and is one of the most sought after specialty by final year African dental students and intending residents. [ 1 2 3 4 ] However, there are little published data about the available specialist training programmes and training pathways available in OMFS in Africa, as there is no document that gives a holistic view of the specialist training of African Oral and Maxillofacial Surgeons. [ 5 6 ] Hence, this study aims to shed some light on the available OMFS specialist training programmes and the different training pathways across Africa.…”
Section: Introductionmentioning
confidence: 99%